Are structural policies in countries bordering mediterranean appropriate to economic convergence: Panel ARDL application - Wajdi Bardi; Saif Eddine Ayouni; Mekki Hamdaoui (Cogent Economics & Finance, 2019)
Our main contribution in this paper consists of analyzing long-run interactions between structural policies and economic growth accounting for possible convergence. For this purpose, we are based on a sample of eight countries bordering the Mediterranean during the period 1975-2012. In fact, we used a technique based on panel ARDL methods which deals with the stationary series problem of different orders to monitor possible convergence in the long-run horizon. This method allows us to study potential long-term effects of structural economic policies on growth as well as capture the possible links between candidate variables and the trend of convergence in terms of per capita GDP. Our empirical results support convergence processes of GDP per capita in all the bordering Mediterranean countries. Moreover, we find that the increased number of secondary schools enrollment through public expenditure on education, greater economic openness, and fluid foreign direct investments stimulates economic growth.
Keywords: 330; convergence; economic policies; mediterranean region; panel autoregressive distributed lag